Intake, digestibility, and ruminal parameters of Nellore bulls supplemented with increasing levels of crude glycerin in Brachiaria Brizantha pastures - Possamai, Adriano Jorge; Zervoudakis, Joanis Tilemahos; Hatamoto-zervoudakis, Luciana Keiko; Freiria, Lucien Bissi Da; Silva, Pedro Ivo José Lopes Da Rosa; Melo, Alan Barbosa (UFBA - Universidade Federal da Bahia, 2017)
SUMMARY We evaluated the effects of increasing levels of crude glycerin in multiple supplements for grazing beef cattle on intake, nutrient digestibility, pH, ruminal ammoniacal nitrogen, and serum glucose. Five Nellore steers (initial BW of 480 kg [SD 15]), grazing a tropical pasture, were used in a 5 × 5 Latin square design. The treatments used were control (no supplementation; only a mineral mixture ad libitum) and four levels of crude glycerin (0, 80, 160, 240 g/kg of supplements). Supplementation type had no impact (P > 0.05) on pH at 0 and 4 h after supplementation. Animals supplemented with different levels of crude glycerin showed higher N-NH3 values (P < 0.05) at 4 h after supplementation. Crude glycerin supplementation did not reduce pasture intake (P > 0.05), increasing dry matter intake (P > 0.05) due to increased organic matter digestibility (P > 0.05). Supplementation of 4 kg/animal with crude glycerin (240 g/kg supplement) did not reduce pasture intake and organic matter digestibility.

RESUMO Objetivou-se avaliar o efeito de níveis crescentes de glicerina bruta em suplementos múltiplos, sobre consumo, digestibilidade dos nutrientes, pH, nitrogênio amoniacal ruminal e glicose sérica. Foram utilizados cinco novilhos, Nelore (peso inicial de 480 kg ± 15), em pastejo de forragem tropical, em delineamento experimental Quadrado Latino 5X5. Os tratamentos utilizados foram controle (apenas suplementação mineral) e quatro níveis de glicerina bruta (0, 80, 160, 240 g/kg de suplemento). Não houve influencia do tipo de suplementação (P>0,05) para pH no tempo zero ou quatro horas após a suplementação. Os animais suplementados com níveis de glicerina bruta apresentaram maior N-NH3 (P>0,05) quatro horas após a suplementação, e o consumo de pasto não foi afetado (P>0,05), com incremento no consumo de matéria seca total (P<0,05), devido o aumento da digestibilidade da matéria orgânica (P<0,05). Os suplementos concentrados fornecidos na quantidade de 4 kg por animal a inclusão de glicerina bruta (240 g/kg de suplemento) não altera o consumo de pasto, suplemento e matéria orgânica digerida.
Consumo, digestibilidade e parâmetros ruminais de machos Nelore não castrados suplementados com níveis crescentes de glicerina bruta em pastagens de “Brachiaria brizantha”
Keywords: crude glycerin; nitrogen ammonia; pH; protein; glicerina bruta; nitrogênio amoniacal; pH; proteína